A temática afro brasileira no contexto da Educação Física escolar - Soares, Dandara de Carvalho [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The choice Brazilian african study theme in the general education, and particularly in physical education has not advanced as to be themed with the subject matter. Even open to this issue, in 2003 a law was passed introducing an obligation of racial ethnic correlations in Brazil. Law 10.639, changed the LDB (Guidelines and Framework Act, 1996) and establishing the obligation both in elementary school as high school, public and private, the teaching of history and African Culture and African Brazilian. As the main objective of disseminating the importance of valuing the African culture and its legacy, expanding the looks and the knowledge about the culture and history of a people who often are discriminated against and excluded by society. The questions that arise are the following: The physical education teacher know that prerogative? Incorporates the Brazilian african discussion in their classes? Discusses with students these subjects related to corporal practices? Have difficulty in dealing with this issue? What? Thus the aim of this study was to detect whether and how a group of physical education teachers is the Brazilian african theme in their classes, for the fulfillment of the Law 10.639 / 03. The methodology of this study was qualitative descriptive type. Were used for data collection semi-structured interviews and non-participant observation. The data obtained through interviews with teachers were transcribed, reviewed and classified according to the content analysis. It is concluded that the racial ethnic theme is not systematically addressed in physical education classes when they are treated, is superficially when proposed by the curriculum of

A escolha do tema do estudo afro brasileiro na Educação de modo geral, e em particular na Educação Física ainda não avançou a ponto de ser tematizada junto aos conteúdos disciplinares. Inclusive, abertas a essa questão, em 2003 foi aprovada uma lei que introduz a obrigatoriedade de correlações étnicas raciais no Brasil. A Lei 10.639, alterou a LDB (Lei de Diretrizes e Bases, 1996) e institui a obrigatoriedade tanto no ensino fundamental quanto ensino médio, público e particular, do ensino de História e Cultura Africana e Afro Brasileira. Com o objetivo principal de divulgar a importância da valorização da cultura africana e seu legado, ampliando os olhares e os conhecimentos acerca da cultura e história de um povo que, muitas vezes, é discriminado e até excluído da sociedade. As questões que se colocam são as seguintes: O professor de Educação Física conhece essa prerrogativa? Incorpora a discussão afro brasileira em suas aulas? Busca discutir com os alunos esses temas relacionados às práticas corporais? Sente dificuldade no tratamento desta temática? Quais? Deste modo o objetivo do presente estudo foi diagnosticar se e como um grupo de professores de Educação Física trata o tema afro brasileiro em suas aulas, para o cumprimento da Lei 10.639/03. A metodologia desse estudo foi de natureza qualitativa do tipo descritiva. Foram utilizados para coleta de dados a entrevista semiestruturada e a observação não participante. Os dados obtidos nas entrevistas com os professores foram transcritos, revistos e classificados a partir da análise de conteúdo. Conclui-se que a temática étnico racial não é abordada sistematicamente nas aulas de Educação Física, quando estas são tratadas, ocorre de forma superficial quando proposto pelo currículo de São Paulo
Keywords: Educação física - Estudo e ensino; Cultura afro-brasileira; Educação; Educação e Estado; Negros - Brasil